2023
DOI: 10.1088/1755-1315/1168/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified cassava flour and purple sweet potato flour formulations on the physical and sensory qualities of meses

Abstract: Tubers are one of the local commodities that must be developed and have several advantages. This study aims to determine the effect of the formulations of mocaf and purple sweet potato flour on the physical and sensory qualities of the meses. Physical qualities include color, hardness, fracture strenght, volume, while the sensory are color, taste, aroma, texture and aftertaste. The research designs used a completely randomized designs with a ratio of mocaf and purple sweet potato flour treatments. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The determined of the formulation was based on previous research by [3] which reported that the best result was sweet potatoes meses with 80% sweet purple potato flour and 20% mocaf flour. This Research prepared using a Complete Randomized Design (CRD), single factor and 3 replication.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The determined of the formulation was based on previous research by [3] which reported that the best result was sweet potatoes meses with 80% sweet purple potato flour and 20% mocaf flour. This Research prepared using a Complete Randomized Design (CRD), single factor and 3 replication.…”
Section: Methodsmentioning
confidence: 99%
“…The fiber content carrots is 2.8% while the fiber content of mocaf is 1.9% [19]. The dietary fiber can influence texture profile meses, [3] report that the higher dietary fiber on mocaf flour caused meses firm.…”
Section: Dietary Fibermentioning
confidence: 97%
See 1 more Smart Citation